Border wars - Barry, Tom, 1950- (Boston review book., 2011)
The Tea Party and its allies celebrate the rogue states of the Southwest as a model for the nation in their go-it-alone posturing and tough immigration-enforcement talk. In Border Wars, dogged investigative journalist Tom Barry documents the costs of that model: lives lost; families torn apart; billions of wasted tax dollars; vigilantes prowling the desert; and fiscal crises in cities, counties, and states. Even worse, he warns, the entire nation risks following their lead. As Barry explains, the lack of coherent federal policy on immigration and drug war conduct and the uncritical embrace of all things in the name of national security has opened doors for opportunists from boardrooms to governor's offices in Texas and Arizona. Corporate-prison magnates eagerly swallow up undocumented immigrants into taxpayer-funded dungeons, border sheriffs and politicians trade on voters' fears of Latinos and "big government," and pro-business policy institutes and lobbyists battle the public interest. Border Wars offers a stark portrait of the domestic cost of failed federal leadership in the post-9/11 era.--Publisher description.